Health systems governance for health equity: critical reflections (2010)
This article addresses several issues pertinent to health systems governance for health equity. It argues the importance of health systems using measures of positive health (well-being), discriminating in favour of historically less advantaged groups and weighing the costs of health care against investments in the social determinants of health. It cautions that the concept of governance could weaken the role of government, with disequalizing effects, while emphasizing the importance of two elements of good governance (transparency and participation) in health systems decision-making. It distinguishes between participation as volunteer labour and participation as exercising political rights, and questions the assumption that decentralization in health systems is necessarily empowering. It then identifies five health system roles to address issues of equity (educator/watchdog, resource broker, community developer, partnership developer and advocate/catalyst) and the implications of these roles for practice. Drawing on preliminary findings of a global research project on comprehensive primary health care, it discusses political aspects of progressive health system reform and the implications of equity-focused health system governance on health workers’ roles, noting the importance of health workers claiming their identity as citizens. The article concludes with a commentary on the inherently political nature of health reforms based on equity; the necessary confrontation with power relations politics involves; and the health systems governance challenge of managing competing health discourses of efficiency and results-based financing, on the one hand, and equity and citizen empowerment, on the other.